2022
DOI: 10.1021/acs.jpcc.2c01403
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Control of the Structural Features and Related Physical Properties of MnxFe3–xO4 Nanoparticles: Implication on Their Heating Performance by Magnetic Hyperthermia

Abstract: Four different manganese ferrite (Mn x Fe3–x O4) nanostructures (9 and 15 nm spheres (S1, S2), 18 nm nanoflowers (NFs), and 20 nm cubes (NC)) were prepared in this work through a thermal decomposition method by tuning the critical synthetic parameters. In all of the prepared materials, the cation composition of the ferrite phase was rather similar. The occurrence of a secondary phase of mangano-wüstite within Mn x Fe3–x O4 nanoparticles and its impact on the magnetic properties were studied in detail from sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…It has been reported that the formation of magnetite by thermal decomposition in organic media is via the oxidation of wüstite, and it has been previously detected in relatively large magnetite NPs prepared under highly reductive environmental conditions, mainly with surfactants such as 1,2-hexadecanediol and solvents like OCT . Under these conditions, the oxidation rate is slower than the growth rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the formation of magnetite by thermal decomposition in organic media is via the oxidation of wüstite, and it has been previously detected in relatively large magnetite NPs prepared under highly reductive environmental conditions, mainly with surfactants such as 1,2-hexadecanediol and solvents like OCT . Under these conditions, the oxidation rate is slower than the growth rate.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the formation of magnetite by thermal decomposition in organic media is via the oxidation of wustite, and it has been previously detected in relatively large magnetite NPs prepared under highly reductive environmental conditions, mainly with surfactants such as 1,2-hexadecanediol and solvents like OCT. 52 Under these conditions, the oxidation rate is slower than the growth rate. Then, depending on the cooling rate and the particle size, the total conversion of wustite and metal iron to magnetite may take place or a small fraction of these phases is preserved in the particle's inner core.…”
Section: Cubic-shaped Mesocrystal Formation: Effect Of the Reaction Timementioning
confidence: 99%
“…Furthermore, as can be seen from Figure 1b, the increase in Cr content leads to a shift in the position of (311) peak towards higher values of 2θ. The results of previous studies of cation-substituted spinel oxides [40,41] have shown that both of these results can be explained by the substitution of larger Mn ions (r Mn = 0.645 Å) by smaller Cr ions (r Cr = 0.615 Å) on the octahedral sites. Moreover, the shift in the (311) peak toward higher angles implies [42] that Cr was incorporated into the crystal lattice of Fe 1.1 Mn 1.9 O 4 .…”
Section: Structural Analysismentioning
confidence: 91%
“…Singh et al [129] reported that the substitution of Mn 2+ ions in magnetite distinctly boosted the SAR value (SAR: 510 kW/kg). Hence, the efficiency of manganese-based hyperthermia agents relies on the concentration of Mn 2+ substitution, site of substitution, particle size, morphology, saturation magnetization, applied magnetic field, frequency, and the dosage of NPs [130]. Some of the manganese-based hyperthermia agents and their SAR values are represented in Table 2.…”
Section: Medical Applicationsmentioning
confidence: 99%